Efficacy Of Ertugliflozin Compared With Metformin Or Placebo In Reducing Hba1c Levels Among Adults With Type 2 Diabetes: A Systematic Review And Meta-Analysis - Permana, Galih Indra; Munthe, Ervi Audina; Irfan, Ihsanul (Green Publisher Indonesia, 2025)
Type 2 diabetes mellitus (T2DM) remains a global health challenge characterized by chronic hyperglycemia due to insulin resistance and impaired insulin secretion. Glycemic control, measured by glycated hemoglobin (HbA1c), is a crucial indicator of therapeutic effectiveness. This systematic review and meta-analysis aim to compare the efficacy of Ertugliflozin, a sodium-glucose co-transporter 2 (SGLT2) inhibitor, with Metformin and Placebo in reducing HbA1c levels among adults with T2DM. Relevant randomized controlled trials (RCTs) published between 2015 and 2025 were identified through PubMed, Scopus, and Cochrane databases. Data extraction and quality assessment followed PRISMA guidelines. The pooled analysis demonstrated that Ertugliflozin significantly reduced HbA1c levels compared to placebo, with mean differences ranging from −0.6% to −1.0% (p < 0.001). When compared to Metformin, Ertugliflozin showed comparable glycemic efficacy, with additional benefits in weight reduction and blood pressure control. Heterogeneity among studies was moderate (I² < 50%), and no severe adverse effects were reported. These findings suggest that Ertugliflozin is an effective and safe alternative or adjunct therapy for adults with T2DM, offering multifaceted metabolic benefits beyond glucose control.